The impact of Mindfulness-based stress reduction on Covid-19 survivors. A randomized controlled trial - Murano, Liana; Damico, Vincenzo; Cossalter, Luca; Riggio, Mario; Calabresi, Fausto; Zappia, Lorenza; Margosio, Viola (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Long-COVID represents a clinical condition characterized by the inability of the patient who survived COVID-19 to regain the same state of health prior to the acute infection. Mindfulness-based stress reduction focuses on increasing awareness and acceptance of moment-to-moment experiences including difficult emotions and physical discomfort. Objective. To examine the effects of a Mindfulness-based stress reduction intervention on the functional and psychosocial outcomes of Long-COVID patients Design. A two-arm randomized controlled trial with repeated-measures design. Setting. Department of Anesthesia and critical care. Participants. COVID-19 survivors (105 patients). Methods. The patients were randomly allocated to either psychoeducation (intervention group) or usual care (control group) (53 vs 52 patients per group). A Mindfulnes program was implemented in the intervention group included an 8-week Mindfulnes-program (2 hours per week) in a group format. Study outcomes included Chronic pain (pain intensity and pain interference) assessed with Brief Pain Inventory (primary outcomes), Anxiety and Depression assessed with Hospital anxiety and depression scale, Insomnia assessed with the Insomnia Severity Index. Data were collected at 6 month and 12 months after Mindfulness-program. Results. A reduction in pain intensity and pain interference on some activities of daily living were observed 6 and 12 months after intervention. A statistically significant difference emerged in the mean score of symptoms of anxiety in favor of the intervention group (11.28 vs 13.15, t= -3.636, p< .001) at 6 month and at 12 months (10.88 vs 13.41, t= -5.167, p< .001) and in the mean score of the symptoms of depression in favor of the intervention group (9.95 vs 11.23, t= -2.823, p= .007) at 6 month and at 12 months (9.67 vs 10.69, t= -2.458, p= .018). Symptoms of insomnia were statistically reduced 6 months after the Mindfulness-program (score: 53.2 vs 30.4, x= 4.944, p= .026).Conclusions. In light of what emerged from our study, we suggest a Mindfulness program in addition to drug therapy to be carried out once a year on patients with consequences of COVID-19. Studies with larger sample sizes that attempt to test a Mindfulness- program twice a year are needed